El Manuscrito de Arquitectura de Vicente de Arizu, Maestro de Obras del siglo XVIII - Azanza López, José Javier (Anuario del Departamento de Historia y Teoría del Arte, 1998)
Vicente de Arizu is a Navarrese architect from the 18th century with an important stock of knowledge that shows in his treatise written in 1778 for his personal use, and which must be known to study the architectonic profession in Navarra in the 18th century. Although his contents are diverse, the chapters about Architecture, Mathematics and Geometry predominate as become an architect. His main source of inspiration is the Compendio Mathematico of Tomás Vicente Tosca, although he also shows his knowledge of Euclides, Viñola, Palladio, Torija or Teodoro Ardemans. His library was also composed by several guides about European towns, among them one of Fioravante Martinelli published in 1702 that includes the monuments from Rome, with shapes of the religious and civil buildings that he reproduced in his treatise. Erudite and traveler, Arizu made two travels to complete his education, one to Zaragoza in 1757 and another to Madrid in 1760, where he analyzed and took notes about the buildings that he contemplated in passing, showing his predilection for the Classicistic Baroque Architecture inheritor of the postulates of Juan de Herrera.